2011
DOI: 10.1111/j.1365-2133.2011.10383.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of methotrexate in severe childhood alopecia areata

Abstract: The efficacy of MTX in children with severe AA is variable. MTX may be considered for severe childhood AA in the absence of alternative effective treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 15 publications
(15 reference statements)
1
60
0
7
Order By: Relevance
“…Recently, the efficacy of MTX has been assessed in children with severe AA in whom all but one initially received oral corticosteroids, suggesting that this initial treatment could influence the course of the disease [16] as suggested previously [13]. This is also in accordance with our results (70% of satisfactory regrowth at month 18), which could suggest that the initial treatment by HDPCT influences the overall response.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, the efficacy of MTX has been assessed in children with severe AA in whom all but one initially received oral corticosteroids, suggesting that this initial treatment could influence the course of the disease [16] as suggested previously [13]. This is also in accordance with our results (70% of satisfactory regrowth at month 18), which could suggest that the initial treatment by HDPCT influences the overall response.…”
Section: Discussionsupporting
confidence: 82%
“…As there is only 1 previous study of MTX use in 6 patients with vitiligo and no studies comparing MTX and OMP, further studies are required to corroborate our results. Also our study used 24 weeks of follow-up; long-term controlled studies with blinded assessment of a larger cohort are required to augment the findings of our study [22,23,24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…2) Prednisone at 10 or 20 mg/day and MTX at 15 mg weekly [79]. 3) Royer et al showed that MTX could be used in children, as a second-line drug with good safety profile [80].…”
Section: Methotrexatementioning
confidence: 99%